Engineering of a peptide ligase from petunia exserta - Doong, Jing Yi (Nanyang Technological University, 2021)
Peptide asparaginyl ligases (PALs) are a rare group of C13 Cys proteases represented by asparaginyl endopeptidases (AEPs). As opposed to the drastic difference in the nature of the activity they carried out, PALs and AEPs share highly similar overall enzyme architecture. The features associated with the desirable ligase activity lie within the non-conserved sites, including sequence variations found in the substrate binding pockets immediately flanking the catalytic site, known as ligase- activity determinants (LADs). In this study, our initial attempt was to convert a PeAEP1 from Petunia exserta to ligase by mutating the LAD1 motif to generate PeAEP1-A233V (PeV). This approach was unsuccessful as PeV proenzyme failed to be activated. In the second attempt, we introduced a double mutant harboring A233V with a point mutation S237P in the poly-Pro-loop (PPL) of which the influence remains unexplored. The double mutant PeAEP1-A233V/S237P (PeVP) underwent successful activation and displayed enhanced ligase activity. Intriguingly, the single mutant PeAEP1-S237P (PeP) remained as a predominant protease, suggesting the enhanced ligase activity in PeVP was the direct influence of mutation A233V while successful autoactivation was facilitated by S237P. Our findings provide deeper insight into the molecular basis of AEPs and PALs and pave the way to the engineering of more AEPs to excellent PALs.